2019
DOI: 10.1111/jcap.12247
|View full text |Cite|
|
Sign up to set email alerts
|

Posttrauma psychosocial effects in children: A systematic review of measurement scales

Abstract: Problem Worldwide, the psychopathological effects of catastrophes such as earthquake, hurricane and war are causing traumas in an enormous number of children. Identification and assessment of the impact on children of catastrophic events is essential to their healing and continued well‐being. Methods To identify the relevant tools Google Scholar, SID, PsycInfo, Medlib, MedLine, and PubMed databases were searched using the relevant Mesh terms and their equivalents including (“anxiety” or “fear” or “depression” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…It is stated that strengthening child‐family communication with positive parental attitudes can also support anger and aggression management and improve emotional wounds in children who experience stress and traumatic events (Atazadeh, Mahmoodi, & Shaghaghi, 2019; Foubister et al, 2020). It has been shown that children who receive emotional support from their families can control their emotions and manage their problematic behaviors such as anger (Bowie, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It is stated that strengthening child‐family communication with positive parental attitudes can also support anger and aggression management and improve emotional wounds in children who experience stress and traumatic events (Atazadeh, Mahmoodi, & Shaghaghi, 2019; Foubister et al, 2020). It has been shown that children who receive emotional support from their families can control their emotions and manage their problematic behaviors such as anger (Bowie, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, exposure to domestic violence is known to be more frequently experienced by children under the age of 6‐year old (Fantuzzo & Fusco, 2007). In addition, the youngest children might be highly vulnerable to the negative consequences of adversity, compared to older children (Atazadeh et al, 2019), especially when they have been exposed to trauma during early childhood, age 0–5 years (Dunn et al, 2017). Vulnerability could be explained in large part by the dependence that very young children show toward adults (Lieberman & Horn, 2009) and could also depend on the ongoing and rapid development of their brain structures (Scheeringa et al, 2005).…”
Section: Contextmentioning
confidence: 99%
“…Integrating varied measures, and adding more comprehensive evaluations to brief screenings tools, such as evaluations taking into account a large and full panel of posttraumatic symptomatology, or permitting a full diagnosis, could make the assessment more specific and sensitive. A comprehensive assessment plays a vital role, since it is through the specific and early identification of their disorder that children can be guided toward the right course of care (Atazadeh et al, 2019; Balaban, 2006; NCTSN, 2018b; Oh et al, 2018). Identifying the different dimensions of expression in a disorder, beyond its nature, allows healthcare professionals to guide children in a specific therapeutic course, but also offers a benchmark as to the effectiveness of a therapeutic action, making it possible to estimate symptomatological changes by proposing a re‐evaluation.…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Social Determinants of Health (SDH) Research Center, Research Institute for Health Development, Kurdistan University of Medical Sciences, Sanandaj, Iran (Atazadeh, Mahmoodi & Shaghaghi, )…”
mentioning
confidence: 99%